Sequential binary decay of highly excited 40Ar* - Nicolis, N. G. (HNPS Advances in Nuclear Physics, 2019)
The sequential statistical binary decay of the highly excited compound nucleus 40Ar* is described with an extended evaporation formalism implemented in a Monte-Carlo multi-step statistical model code. Asymmetric mass splittings involving nucleon emission up to symmetric binary ones are treated within the evaporation formalism, in a unified manner. Emission of heavy fragments in their ground and excited (particle-bound or unbound) states is considered. The evolution of the final mass distributions from 40Ar* is studied as a function of the initial excitation energy, in the range from 45 up to 405 MeV. The population of final states originating from the decay of intermediate mass fragments in particle-bound and particle-unbound states (side-feeding) is discussed. Results are compared with an alternative description in which the time-dependent decay process is described by rate equations for the generation of different fragment species.